European Society of Coloproctology: guidelines for the management of diverticular disease of the colon. (7th July 2020) - Schultz, J. K.; Azhar, N.; Binda, G. A.; Barbara, G.; Biondo, S.; Boermeester, M. A.; Chabok, A.; Consten, E. C. J.; van Dijk, S. T.; Johanssen, A.; Kruis, W.; Lambrichts, D.; et al.
Abstract: Aim: The goal of this European Society of Coloproctology (ESCP) guideline project is to give an overview of the existing evidence on the management of diverticular disease, primarily as a guidance to surgeons. Methods: The guideline was developed during several working phases including three voting rounds and one consensus meeting. The two project leads (JKS and EA) appointed by the ESCP guideline committee together with one member of the guideline committee (WB) agreed on the methodology, decided on six themes for working groups (WGs) and drafted a list of research questions. Senior WG members, mostly colorectal surgeons within the ESCP, were invited based on publication records and geographical aspects. Other specialties were included in the WGs where relevant. In addition, one trainee or PhD fellow was invited in each WG. All six WGs revised the research questions if necessary, did a literature search, created evidence tables where feasible, and drafted supporting text to each research question and statement. The text and statement proposals from each WG were arranged as one document by the first and last authors before online voting by all authors in two rounds. For the second voting ESCP national representatives were also invited. More than 90% agreement was considered a consensus. The final phrasing of the statements with < 90% agreement was discussed in a consensus meeting at the ESCP annual meeting in Vienna in September 2019. Thereafter, the first and the last author drafted the final text of the guideline and circulated it for final approval and for a third and final online voting of rephrased statements. Results: This guideline contains 38 evidence based consensus statements on the management of diverticular disease. Conclusion: This international, multidisciplinary guideline provides an up to date summary of the current knowledge of the management of diverticular disease as a guidance for clinicians and patients.